2017 Update on Ovarian Cancer Peritoneal Carcinomatosis Multimodal-Treatment Considerations. (5th April 2018) - Halkia, Evgenia; Chrelias, George; Chrelias, Charalambos; Esquivel, Jesus
Abstract : Ovarian cancer peritoneal carcinomatosis requires a multimodal-treatment approach. Current treatment considerations are analyzed in this update and include the management of recurrent malignant ascites and the understanding of its pathophysiology, the role of peritoneal washing cytology in detecting peritoneal metastases, capsular invasion and ovarian cancer histologic type, interpretation of pretreatment Ca-125 levels at different time points of ovarian cancer therapeutic management, characteristics of 10-year survivors of high-grade ovarian cancer, and the role of lymphadenectomy in ovarian cancer peritoneal carcinomatosis. This update also includes current considerations on the role of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in ovarian cancer peritoneal carcinomatosis as well as relevant ongoing phase III randomized controlled trial protocols.